Pengaruh Konten Promosi Wisata pada Akun Instagram @kotalamasurabaya Terhadap Minat Berkunjung Wisatawan - Zefanya, Aulia Neva; Mustikasari, Ratih Pandu (Universitas Prof. Dr. Moestopo (Beragama), 2026)
This study was motivated by the development of Kota Lama Surabaya as a heritage tourism destination, which was officially launched in July 2024. As a new tourist destination, effective promotional strategies are needed to increase tourist interest. One of the promotional media used is the Instagram account @kotalamasurabaya. However, the effectiveness of promotional content in influencing visitor interest has not been empirically researched. This study uses a quantitative approach with an explanatory research design. The research population consists of followers of the @kotalamasurabaya Instagram account, with the sample determined using purposive sampling, namely active Instagram users aged 17–35 years who follow the account. Data were collected through an online questionnaire using a 1–4 Likert scale and analyzed using SPSS version 27. This study uses the Stimulus–Organism–Response (S–O–R) theory to explain the influence of promotional content on audience response and interest in visiting. The results show that promotional content influences tourists' interest in visiting through the aspects of relevance, accuracy, ease of understanding, and ease of access to information.